Systematic neonatal pain evaluation in the delivery room: Does it matter?. Issue 1 (February 2023) - Walter-Nicolet, Elizabeth; Moussa, Ouyssal; Bolot, Pascal
Abstract: Neonatal pain assessment in the maternity ward is insufficient and not systematic. The aim of our study was to show that a systematic neonatal pain assessment in the delivery room would led to a 2-fold relative increase in the pain diagnosis rate. We also hypothesised that some overdiagnosed neonates would receive unnecessary acetaminophen treatment. We prospectively included 96 neonates and evaluated all of them with three scales: Neonate Pain and Discomfort Scale (Echelle Douleur et Inconfort du Nouveau-né) (EDIN), reduced Neonatal Facial Coding System (4 items-NFCS) and an attributed Numeric Rating Scale (NRS-11). A systematic assessment led to a 4-fold relative increase in the pain diagnosis rate. The correlation with the scales used were good. Our study did not show an excessive use of acetaminophen treatment.